2017
DOI: 10.1556/168.2017.18.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Cannibalism: Do risks of fighting and reprisal reduce predatory rates?

Abstract: Cannibalism is a common phenomenon among insects. It has raised considerable interest both from a theoretical perspective and because of its importance in population dynamics in natural ecosystems. It could also play an important role from an applied perspective, especially when using predatory species in biological control programmes. The present paper aims to study the cannibalistic behaviour of Nabis pseudoferus Remane and the functional response of adult females. In a non-choice experiment, adult females s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Although Nabis exhibits more complex behaviour than our theoretical model, we found that the cannibalistic Nabis uses a search image but not with absolute intention because it can also encounter non-desired prey types; however, the its encounter sequence is not determined by the preys’ densities, i.e., Nabis encounters its preferred prey with a higher probability than its potential conspecific prey. This finding corroborates results on the subject that have been published elsewhere 29 .…”
Section: Experimental Study: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Although Nabis exhibits more complex behaviour than our theoretical model, we found that the cannibalistic Nabis uses a search image but not with absolute intention because it can also encounter non-desired prey types; however, the its encounter sequence is not determined by the preys’ densities, i.e., Nabis encounters its preferred prey with a higher probability than its potential conspecific prey. This finding corroborates results on the subject that have been published elsewhere 29 .…”
Section: Experimental Study: Resultssupporting
confidence: 93%
“…pseudoferus exhibit a type II functional response. In general, other Nabis species also present type II responses in their nymph and adult stages 29 . On the other hand, cannibalism in N .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such behavior in predatory Nabis species was observed when they were attacking larger, phytophagous species (e.g., Spodoptera exigua (Hübner), Lep. : Noctuidae) [103].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Aljetlawi et al (2004) derived a functional response function that accounted for both predator and prey size. Furthermore, Cabello et al (2007) introduced new expressions for Holling type III in terms of a new parameter called entomophagous potential (of a parasitoid or predator), which is important from the view point of biological pest control (e.g., Fernandez-Maldonado et al 2017).…”
Section: Deterministic Methods For Decreasing Prey Density Without Timmentioning
confidence: 99%